PENGARUH KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KARYAWAN LKP LESTARI KOMPUTER SLAWI - Sri Lestari; Joko Mariyono (Multiplier: Jurnal Magister Manajemen, 2017)
Employee Performance is one of factors as the determiner to improve the quality of students. Thus, employee performance should get the attention and support seriously from any sides, especially from component of human resources institution. The expectation is it will improve the motivation of employee that impact on the result of the students’ achievement. The goals of the research are (1) to desrcibe the leadership, job satisfaction, motivation and employee performance, (2) to know the influnces of leadership and job satisfaction toward employee motivation, (3) to know the influences of leadership and job satisfaction toward employee performance, (4) to know the influences of motivation toward employee performance, (5) to know the influnces of leadership and job satisfaction toward performance through employee motivation. The participants in this research are 37 people. These participants are the employee of LKP Lestari Komputer Slawi. The data is analyzed by Structural Equation Modeling (SEM) using AMOS 18.00 as analysis tool. The results of Standardized Regression Coefficient were shown that the leadership and job satisfaction has influenced significantly on the employee motivation (0,27), job satisfaction toward employee satisfaction (0,55), leadership toward employee performance (0,41), job satisfaction toward employee performance (1,00). The results of p-value were also shown that motivation has influenced toward employee performance (<0,001). Keywords : leadership, satisfactory, motivation, and performance